SISTEM PAKAR REKOMENDASI JURUSAN DI SMK BERBASIS LARAVEL DENGAN METODE RULE-BASED REASONING DAN FORWARD CHAINING - Agung Dumadi; Ahmad Munawir; Wahyu Amaldi (Universitas Majalengka, 2025)
The choice of major at the vocational high school level is a crucial factor influencing students' motivation, academic achievement, and future careers. However, the manual selection process often lacks objectivity and efficiency. This study designs and develops a web-based expert system for major recommendation using the Laravel framework with a rule-based reasoning approach. The system includes student biodata input, an interest questionnaire, a forward chaining inference engine, and an interactive admin dashboard. Development used the Waterfall model, while black-box testing and user acceptance testing (UAT) ensured accuracy and user acceptance. Test results show the system provides major recommendations matching student profiles, with additional details such as major descriptions, job prospects, and interest score visualizations. Furthermore, the UAT user satisfaction rate reached 85.25%, indicating the system is feasible to support a digital and objective major selection process.